Urgensi Sadar Lingkungan di Era Teknologi - Juanda Tiolopan Hutahaean; Masduki Asbari; Freddy Nurwanto (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this study is to find out how to encourage the younger generation to innovate and provide impacts and solutions, not only for society, but also for the environment. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from Achmad Zaky's YouTube channel entitled